Safe Motherhood: Morbidity and Mortality Associated with Unsafe Termination of Pregnancy (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the morbidity and mortality associated with unsafe termination of pregnancy.Material and Methods: A cross sectional descriptive study was conducted in the Department of Obstetrics and Gynaecology at Sir Ganga Ram Hospital, Lahore from January 2008 to March 2014. A total of 139 patients who presented with history of termination of pregnancy with instruments were included in the study. Data regarding their socio demographic features, reason for termination of pregnancy, nature of provider/facility, complications and treatment were collected and analysed.Results: A total of 139 women who underwent instrumental termination of pregnancy were included in this study. Majority of them were married (98%). Multigravida constituted 54% of the patients while 46% were primigravida. The most common complaint was fever (26%) while 21% presented with abdominal distension and acute abdomen. Mortality among the subjects was 17%.The most frequent complication was uterine perforation (65%) followed by pelvic abscess (32%) and septicaemia (26%). All termination of pregnancies was performed by untrained providers. An unwanted pregnancy was the main reason (58%) while 42% underwent instrumentation due to irregular vaginal bleeding.Conclusion: The high maternal morbidity and mortality associated with unsafe termination of pregnancy in our study highlights the importance of providing safe post abortion care to our women and the need to improve contraceptive practices in our set up.